Struktur Morfologis Penamaan Wilayah di Kabupaten Maros - Fitrawahyudi, Fitrawahyudi; Fadli, Irwan; Aryanti, Aryanti (Jubindo: Jurnal Ilmu Pendidikan Bahasa dan Sastra Indonesia, 2022)
This study aims to describe and examine the value of moral education in the novel Wedding Agreement. The method used in this research is descriptive qualitative. This novel has the theme of marriage through an arranged marriage. The subject in this research is Moral Education Value, while the object is the Wedding Agreement novel. the results of the analysis found the value of moral education towards God, namely (1) obeying God (belief in God, praying, praying, thanking), (2) being content with His provisions (ikhas), (3) putting your trust in Him (surrendering). . Furthermore, the value of moral education to creatures. The first is the value of moral education to parents, namely (1) saying politely, (2) respecting parents. The two values of moral education to friends are (1) affection, (2) asking how they are. Finally, the value of moral education on the association of the opposite sex, namely (1) avoiding adultery, (2) maintaining aurat. Keywords: Moral Education, Sastra, Novel Wedding Agreement